2022
DOI: 10.3389/fmicb.2022.852036
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pneumoniae Affects Endothelial Cell Migration in Microfluidic Circulation

Abstract: Bloodstream infections caused by Streptococcus pneumoniae induce strong inflammatory and procoagulant cellular responses and affect the endothelial barrier of the vascular system. Bacterial virulence determinants, such as the cytotoxic pore-forming pneumolysin, increase the endothelial barrier permeability by inducing cell apoptosis and cell damage. As life-threatening consequences, disseminated intravascular coagulation followed by consumption coagulopathy and low blood pressure is described. With the aim to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…), etc., which revealed that some of the most common autoantigen targets in COVID-19-associated coagulopathies, such as CL, PF4 and β2GP, have significant mimics with these bacteria but do not have significant mimics with SARS-CoV-2 and especially its spike protein [ 40 ] (summarized in Figure 1 ). Since some bacterial infections, especially GAS , Staphylococci, Klebsiella and Clostridia , are themselves associated with increased risks of coagulopathies [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ], these results suggested that preceding or concomitant bacterial co-infections may support the induction of a variety of COVID-19 autoimmune coagulopathies through anamnestic secondary cross-reactivity or bystander activation of complementary autoimmune mechanisms to those activated by SARS-CoV-2. Conversely, if a pre- or co-existing bacterial infection were necessary to induce autoimmune coagulopathies, then the absence of such infections among the vast majority of vaccinees might explain the extremely infrequent occurrence of vaccine-induced thrombotic events [ 62 , 63 ].…”
Section: Introductionmentioning
confidence: 99%
“…), etc., which revealed that some of the most common autoantigen targets in COVID-19-associated coagulopathies, such as CL, PF4 and β2GP, have significant mimics with these bacteria but do not have significant mimics with SARS-CoV-2 and especially its spike protein [ 40 ] (summarized in Figure 1 ). Since some bacterial infections, especially GAS , Staphylococci, Klebsiella and Clostridia , are themselves associated with increased risks of coagulopathies [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ], these results suggested that preceding or concomitant bacterial co-infections may support the induction of a variety of COVID-19 autoimmune coagulopathies through anamnestic secondary cross-reactivity or bystander activation of complementary autoimmune mechanisms to those activated by SARS-CoV-2. Conversely, if a pre- or co-existing bacterial infection were necessary to induce autoimmune coagulopathies, then the absence of such infections among the vast majority of vaccinees might explain the extremely infrequent occurrence of vaccine-induced thrombotic events [ 62 , 63 ].…”
Section: Introductionmentioning
confidence: 99%